Family Quality Time for Employees Working From Home. Before and During COVID-19 Pandemic Comparisons - Tufă, Laura A.; Neguț, Adriana (Calitatea Vieții, 2023)
Data from a two-wave study (2018−2019 and 2020) on working conditions and on work-life balance for those working from home (WFH) point to the fact that the contribution of WFH to family quality time is distinct when gender, children and different levels of education are considered. Our first wave showed that for those who do not have children, the more they work from home, the greater the extent to which they agree that “WFH allows more quality time with the familyˮ. For men, WFH does not change the representation of quality time with the family. Implications point to an unequal representation and distinct gendered experiences of quality family time that hide different time use patterns in family members, with an even more clear division with the cultural shift around work generated by the current pandemic. Men tend to be more protected from household chores and possibly have different standards of what quality time means, which would explain our results. Moreover, data from 2020 suggests that the appreciation of WFH as contributing to quality family time is lower than the 2018−2019 data suggested, even when we control for education, age, number of children, living in Romania or outside it, gender, and number of members in the household. This further expands the discussion about different theoretical conceptualisations of quality family time, and about how the COVID-19 pandemic, with forced and sudden working from home policies, contributed to a deterrence of home as a restorative place.